Children's perceptions of their parent's parenting strategies and child influence on purchases in a supermarket. (1st July 2021) - Castro, Iana A.; Poor Miles, Morgan; Gonzalez, Gabriel R.; Ayala, Guadalupe X.
Abstract: This field study identified, through observation, child influence on food and beverage purchases within a supermarket, as well as the influence of the children's perceptions of their parents' parenting strategies related to eating behaviors on these purchases. Four supermarkets were recruited to participate and agreed to allow recruitment of parent-child dyads and implementation of data collection protocols within their stores. Parent-child (7–14 yo) dyads were recruited to wear eye-tracking glasses during the supermarket visit, complete separate individual interviews, and have their store receipts scanned. The receipt data provided evidence of what was purchased, including overall purchases, as well as purchases of energy-dense, nutrient-poor foods and beverages. The eye-tracking data, together with the receipt data, identified which items were requested by the child and purchased. The child interviews provided the child's perceptions of parenting strategies (i.e., parental monitoring, control). Seventy-six dyads agreed to participate and completed the study protocols. During most of the shopping trips, items were purchased as a result of child-initiated request interactions. Children's perceptions of their parent's use of monitoring was consistently associated with fewer purchases overall and of energy-dense, nutrient-poor items, and with reduced child influence on what was purchased.